Dilemma of Distance Learning Policies in the Cultural Framework of Early Marriage in Ambunten-Sumenep, East Java - Hanik, Umi; Tannisyafolia, Ratih Himamatul Azizah; Ningtyas, Trimurti (Didaktika Religia, 2022)
During the distance learning period, according to data from the BKKBN Sumenep District, cases of early marriage have increased. This study discusses the effect of distance learning policies implemented in Indonesia during the pandemic period, namely at the end of 2019 to 2021 on cases of early marriage in Ambunten District, Sumenep Regency, East Java. This study uses primary data from the results of interviews with children who married early in December 2019 to April 2021, namely 5 informants who married at an early age. In addition, researchers made observations about the implementation of distance learning and early marriage there. It was found that distance learning is a stimulus that the culture of early marriage in Sumenep District which they believe is worth doing to minimize the impact of young people's association, namely adultery. The lack of parental role in distance learning assistance, as well as environmental and structural support for early marriage, makes students make marriage a primary choice rather than school. In addition, early marriages that take place occur due to several factors, namely culture, family, and economy.